New technological developments in medical education - Beniamin Michalik; Michał Sęk; Aleksandra Szypuła; Katarzyna Hajduk-Maślak; Adrianna Skóra; Iwona Galasińska (Kazimierz Wielki University, 2024)
Introduction: Medical education is a rapidly evolving field, necessitating adaptation to shifts in student demographics and societal needs. Balancing the demand for more healthcare providers must be accompanied by a focus on maintaining the quality of education. As certain conventional teaching methods lose favour, there is a continuous influx of new technologies that can be harnessed for the education of future doctors. Purpose of the study: The objective of this study was to gather and analyse literature on the utilization of new technologies in medical education and their influence on students, educators, and the overall quality of medical instruction. Material and methods: A review of the literature available on PubMed and a grey literature search was performed. We used such keywords like: "medical education", "physician training", "medical students", "technology", "elearning", "new learning methods". We also applied Bolean logical operators such as "AND", "OR".   Results: Examining the gathered publications leads to the conclusion that a variety of new technologies are being employed in medical education, such as e-learning, telehealth, and virtual or augmented reality. While some function as alternatives to existing methods, others introduce entirely novel approaches. In general, these new technologies positively impact education by enhancing outcomes, increasing accessibility to education, and reducing the costs associated with the teaching process. Conclusions: The integration of emerging technologies has become essential in the preparation of future medical professionals. Despite the overall positive impact, there are apprehensions regarding potential long-term consequences for healthcare delivery. Subsequent studies are crucial to assess lasting effects, delving into how the integration of technology may shape the skills of healthcare professionals over time.